2023
DOI: 10.1111/aphw.12470
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the theory of planned behavior and the self‐determination theory to promote Mediterranean diet adherence: A randomized controlled trial

Abstract: The Mediterranean diet (MD) is one of the healthiest and most sustainable food regimes. Nevertheless, MD diffusion is still limited, emphasizing the need to understand the psychosocial factors that could predict and promote its adoption. Starting from an integrated model of Theory of Planned Behavior (TPB) and Self‐Determination Theory (SDT), the present randomized controlled trial investigated the effect of manipulating motivation (autonomous vs. controlled) on intention and MD adherence behavior. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…These metacognitive abilities, which encompass modifying behaviors, thoughts, emotions, and environmental interactions, are pivotal in achieving personal health goals. Previous studies have supported that metacognition is associated with various healthy lifestyle behaviors, such as regular physical activity, screen time management, and adherence to a Mediterranean diet [39][40][41] . Studies with fMRI have demonstrated that the FPC, speci cally Brodmann area 10, was also activated during metacognitive tasks that involve self-evaluation and decision-making 42 .…”
Section: Discussionmentioning
confidence: 95%
“…These metacognitive abilities, which encompass modifying behaviors, thoughts, emotions, and environmental interactions, are pivotal in achieving personal health goals. Previous studies have supported that metacognition is associated with various healthy lifestyle behaviors, such as regular physical activity, screen time management, and adherence to a Mediterranean diet [39][40][41] . Studies with fMRI have demonstrated that the FPC, speci cally Brodmann area 10, was also activated during metacognitive tasks that involve self-evaluation and decision-making 42 .…”
Section: Discussionmentioning
confidence: 95%